The pathogenic p.Gln319Ter variant is not causing congenital adrenal hyperplasia when inherited in one of the duplicated CYP21A2 genes - Fanis, Pavlos; Skordis, Nicos; Toumba, Meropi; Picolos, Michalis; Tanteles, George A.; Neocleous, Vassos; Phylactou, Leonidas A. (Frontiers in Endocrinology, 2023)
Objective: The study aimed to identify the pathogenic status of p.Gln319Ter (NM_000500.7: c.955C>T) variant when inherited in a single CYP21A2 gene (bimodular RCCX haplotype) and to discriminate between a benign allele when inherited in a duplicated and functional CYP21A2 gene context (trimodular RCCX haplotype). Methods: 38 females and 8 males with hyperandrogenemia, previously screened by sequencing and identified as carriers for the pathogenic p.Gln319Ter, were herein tested by multiplex ligation-dependent probe amplification (MLPA) and a real-time PCR Copy number Variation (CNV) assay. Results: Both MLPA and real-time PCR CNV analyses confirmed a bimodular and pathogenic RCCX haplotype with a single CYP21A2 in 19/46 (41.30%) p.Gln319Ter carriers and who in parallel all shared elevated 17-OHP levels. The remaining 27 individuals had low 17-OHP levels and carried a non-pathogenic p.Gln319Ter variant in a duplicated CYP21A2 with a trimodular RCCX haplotype. Interestingly, all of these individuals also carried in linkage disequilibrium with p.Gln319Ter two single nucleotide polymorphisms, the c.293-79G>A (rs114414746) in intron 2 and the c.*12C>T (rs150697472) in the 3’-UTR. Therefore, these variants can be used to distinguish between pathogenic and non-pathogenic genomic contexts of the c.955T (p.Gln319) in the genetic diagnosis of congenital adrenal hyperplasia (CAH). Conclusion: The employed methodologies identified a considerable number of individuals with non-pathogenic p.Gln319Ter from the individuals that typically carry the pathogenic p.Gln319Ter in a single CYP21A2. Therefore, it is extremely important the detection of such haplotypes for the prenatal diagnosis, treatment and genetic counseling in patients with CAH.